Naegleria fowleri in Central and South America: The brain-eating amoeba is it in Peru? - Cabello-Vilchez, Alfonso Martin (2023)
Free-living amoebae (FLA) are microbial entities that are capable of causing disease in humans and animals. Naegleria fowleri is one of the three free-living amoebae that are pathogenic to humans; it has been identified in the South American continent. Peru has reported only one case in 2015. This case has not been published, only notified to the Ministry of Health. The girl under 11 years old and was infected in Piura, north coast of Peru. Patients die after 5-7 days, that is, it is an acute course. Latin countries such as Argentina, Brazil, Venezuela and Colombia describe 1, 5, 7 and 6 cases respectively. In this review, we will describe various aspects of this amoeba. Morphology, ecology, pathology, epidemiology, adequate culture media, and microbiological and molecular diagnoses. In addition, the relationship with the phenomenon “El Niño” and the appearance of cases of meningitis.